(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
Introduction: The validation and use of VARK scoring system in determining preferred sensory modalities for learners have evolved with time in many countries. American University of Nigeria, through the Teaching and Learning Center is poised at improving its teaching methods and practices to cater for the diverse learning styles of students. This study therefore, was to identify the learning style preferences of students using VARK questionnaire. Methodology: A cross-sectional survey of all enrolled American University students totaling 1493. Standardized 16 questions VARK questionnaire was used to collect data on visual preference, aural preference, read/write preference and kinesthetic preference and analyzed using Google form and SPSS version 31. Result was presented in tables and figures with multivariate analysis of variance used to test for association between age, gender, school of study and VARK preferences at p-value 0.05. Results: Overall preferences result showed a multimodal learning style among AUN students. A little over two-third of the population of respondents fit into this multimodal preferences group. There were levels in VARK preferences according to gender, age and course of study with most students gravitating towards multimodalities of learning preferences particularly in aural and kinesthetic styles. Gender, age and school of study of respondents were not significantly associated with learning style preferences (p<0.05). However, increasing age (>22 years) has an affinity towards adopting higher limits of learning style preferences by learners. Conclusion: The dominance of multimodal preferences among AUN students, confirms that an integrated approach, with multisensory pedagogy is best suited for learners. The choice of VARK in American University of Nigeria depict the peculiarity of students learning preferences. Researchers recommend adoption of multimodal approach that customizes pedagogy by discipline, while diversifying assessments to engage all VARK modes. Key words: VARK, Learning style preferences, Students, American University of Nigeria